Hematological Study of Infants Amoebiasis in Duhok City - Baghdad Science Journal (مجلة بغداد للعلوم)
Out of 180 children, 60 (33.3%) have Amoebiasis infection as diagnosed by direct wet smear and Saturated Salt Solution (SSS). SSS method is more significant (P=0.001) in diagnosis of the disease. Number of children infected with Amoebiasis infection is higher in infants aged 1-6 months, but without any significant difference to ages 6-12 or 12-18 months. In contrast, infants aged 18-24 months are significantly differant (P=0.01) as the infection rate is 16.6%. Gender also is seen to be reduced in significance (P= 0.001) for females aged 18-24 months. Blood profile of the involved infants has shown a significant variation (P=0. 01) for all blood profile parameters (RBC (P=0.05), WBC (P=0.001), Lymphocytes (P=0.05), Granulated WBC (P=0.05), Hb (P=0.01) and Platelets counts (P=0.001). Many medicinal regimes are dependent in the treatment of Amoebiasis, Metronidazole (Flagyl) in significant variation (P=0.01), combination of Metronidazole and Bactrim